PENJADWALAN MATA KULIAH MENGGUNAKAN ALGORITMA GENETIKA DI STT WASTUKANCANA PURWAKARTA - Umar Hasan; Teguh Iman Hermanto; M. Rafi Muttaqin (Jurnal Teknologi dan Informasi (JATI), 2018)
Generating a study at STT Wastukancana Purwakarta is strongly important to get an effective way to study. As the allocation of rooms to the schedule made is still manual, it is possible there are some room service clashes. To solve that problem, a study scheduling using computerization is needed in order to make no clash of room service. The use of genetic algorithm to solve the problem is able to get the optimal solution in generating the schedule with chromosome representative as an integer from each of data primary key, the beginning of population initialization, the selection with rank-selection method, two-points crossover method, and mutation. From the test, the result points out that the optimal schedule with 416 pengampu data is generated when a number of population are 30, a number of generations are 150, the crossover probability value (Pc) is 0.4, and the mutation probability value (Pm) is 0.37.